Digital animation for 'going public' on curriculum integration of HIV & AIDS in higher education - Pithouse-Morgan, Kathleen; van Laren, Linda; Mitchell, Claudia; Mudaly, Ronicka; Singh, Shakila (South African Journal of Higher Education, 2016)
An interdisciplinary team of researchers sought ways of encouraging discussion, reflexivity and generative thinking around HIV & AIDS integration in higher education curricula. We facilitated conversations in three higher education research settings through the medium of a digital animation based on a storyboard prepared in response to experiences of university educators who integrate HIV & AIDS-related issues in their teaching. We screened the digital animation and encouraged responses from the three audiences, then used these responses together with our own deliberations to explore the ‘what’ and ‘how’ of making public our work. Using digital animation for generative action, we found that the four conceptual and methodological features of generative processes (playfulness, passion, perspicacity and participation) that we identified through previous research may be extended to a fifth – that of publicising research, or ‘going public’, which played an important role in our innovative and responsive use of digital animation.